Effects of Wearing Face Masks While Using Different Speaking Styles in Noise on Speech Intelligibility During the COVID-19 Pandemic - Yi, Hoyoung; Pingsterhaus, Ashly; Song, Woonyoung (Frontiers in Psychology, 2021)
The coronavirus pandemic has resulted in the recommended/required use of face masks in public. The use of a face mask compromises communication, especially in the presence of competing noise. It is crucial to measure the potential effects of wearing face masks on speech intelligibility in noisy environments where excessive background noise can create communication challenges. The effects of wearing transparent face masks and using clear speech to facilitate better verbal communication were evaluated in this study. We evaluated listener word identification scores in the following four conditions: (1) type of mask condition (i.e., no mask, transparent mask, and disposable face mask), (2) presentation mode (i.e., auditory only and audiovisual), (3) speaking style (i.e., conversational speech and clear speech), and (4) with two types of background noise (i.e., speech shaped noise and four-talker babble at −5 signal-to-noise ratio). Results indicate that in the presence of noise, listeners performed less well when the speaker wore a disposable face mask or a transparent mask compared to wearing no mask. Listeners correctly identified more words in the audiovisual presentation when listening to clear speech. Results indicate the combination of face masks and the presence of background noise negatively impact speech intelligibility for listeners. Transparent masks facilitate the ability to understand target sentences by providing visual information. Use of clear speech was shown to alleviate challenging communication situations including compensating for a lack of visual cues and reduced acoustic signals.